99Tc‐ and 239Pu‐Doped Glass Leaching Experiments: Residual Alteration Rate and Radionuclide Behavior. (25th October 2013) - Rolland, Séverine; Tribet, Magaly; Jégou, Christophe; Broudic, Véronique; Magnin, Magali; Peuget, Sylvain; Wiss, Thierry; Janssen, Arne; Blondel, Antoine; Toulhoat, Pierre
<x xml:space="preserve">Abstract</x> The long‐term behavior of high‐level nuclear glass subjected to alpha/beta radiation by long‐life radionuclides must be investigated with respect to geological disposal. This study focuses on the effects of alpha and beta radiations on the chemical reactivity of R7T7 glass with pure water, mainly on the residual alteration rate regime. Glass specimens doped with 0.85 wt% 239PuO2 (α emitter) and 0.24 wt% 99TcO2 (β emitter) that simulate alpha and beta dose rate corresponding to long‐term disposal conditions are leached under static conditions in argon atmosphere at 90°C, in initially pure water and at a high surface‐area‐to‐volume ratio (S/V = 20/cm). The alteration rate is monitored by the release of glass alteration tracer elements (B, Na, and Li). Radiation effects on the leached glass and its gel network are characterized by SEM and TEM analyses. Plutonium and technetium releases are also measured by radiometry, and their chemical oxidation state is assessed by measuring the pH and reduction–oxidation potential of the leachates. The results do not highlight any significant effect of alpha/beta radiation on the residual alteration of these doped glasses. These observations are consistent with solid characterizations, which show that a protective layer can be formed under such irradiation fields. Under our experimental conditions (Eh 380 mV/SHE, pH90°C = 8–8.6), very low concentrations of soluble plutonium are measured in the leachate, indicating strong plutonium retention, whereas technetium performs as a soluble element and is not retained in the altered layer.